1989
DOI: 10.1111/j.1365-2257.1989.tb00205.x
|View full text |Cite
|
Sign up to set email alerts
|

Combination chemotherapy with conservative obstetric management in the treatment of pregnant patients with acute myeloblastic leukaemia

Abstract: We have reviewed the management of pregnant women presenting with acute myeloblastic leukaemia (AML) at the London Hospital since 1972. Six women in the second or third trimester were diagnosed with AML over this period. One woman had termination of pregnancy at presentation in the second trimester. Three of the remaining five patients achieved complete remission following chemotherapy during pregnancy. Delivery was achieved by the vaginal route in three and by caesarean section in one patient. All were livebi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…However, there is general agreement concerning the initiation of induction therapy in the 2nd-3rd trimesters. Good results are often obtained at a standard or moderately aggressive dose rather than a smaller dose (Bartsch et al 1988;Caligiuri and Mayer 1989;Feliu et al 1988;Gondo et al 1990; Roy et al 1989). In the treatment of pregnant patients with leukemia, a detailed protocol is needed based on the month of pregnancy, avoiding the use of alkylating drugs and antifolic agents and the combination with irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is general agreement concerning the initiation of induction therapy in the 2nd-3rd trimesters. Good results are often obtained at a standard or moderately aggressive dose rather than a smaller dose (Bartsch et al 1988;Caligiuri and Mayer 1989;Feliu et al 1988;Gondo et al 1990; Roy et al 1989). In the treatment of pregnant patients with leukemia, a detailed protocol is needed based on the month of pregnancy, avoiding the use of alkylating drugs and antifolic agents and the combination with irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Reynoso et al, 2 in a review, documented 77% complete remission rates in acute myeloid leukemia, figures similar to the complete remission rates achieved in the nonpregnant patients. Roy et al, 3 in a study of six patients, achieved a complete remission rate of 66%, a rate comparable to one achieved in nonpregnant patients treated with similar protocols; the more aggressive regimens were associated with better survival. Our patient, treated with an intensive combination chemotherapy in standard dosage, confirms this observation.…”
Section: Discussionmentioning
confidence: 80%
“…5 The use of cytotoxic therapy in the second and third trimesters of pregnancy have not been shown to induce fetal malformation. 2,3,[5][6][7] In our patient, who had twin pregnancy, neither fetus showed any malformations. Juarez et al 6 have reported one case of twin pregnancy associated with leukemia; however, it was accompanied by premature labor and both fetuses were dead.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other adverse effects to the newborn included myelosuppression, hepatopathy, elevated CK, seizures, acrocyanosis, hyaline membrane disease, moderate meningeal hemorrhage, respiratory distress symptoms, and infections. Two cases (case 17 and 19) have reported chromosomal abnormalities: Down's syndrome 25 and inversion on chromosome 9. 36 Growth defects were observed in 4 infants.…”
Section: Resultsmentioning
confidence: 99%